Youth Realities and Aspirations - Herbert J. Walberg; Rebecca Greenberg (Journal of Research in Rural Education, 1996)
The preceding papers provide a splendid set of findings and insights, a basis of important implications for education policies and practices, and a store of ideas for further research. The purpose of this commentary is to characterize the severe problems faced by American youth, and to comment on papers individually and as a set.